'Distant Reading' in French Music Criticism. Issue 2 (26th August 2022) - Joubert, Estelle
Abstract : This article offers a series of experiments exploring the potential for 'distant reading' in French music criticism. 'Distant reading', a term first coined by literary theorist Franco Moretti, refers to quantitative approaches that allow for new insights into a large corpus of texts by aggregating data. While the main corpus employed here is the Revue et gazette musicale de Paris (1831–1877), I also use secondary corpora of reviews of Félicien David's Herculanum in 1859, Berlioz's reviews of Gluck and Beethoven in the Journal des débats and reviews that mention Gabriel Fauré in the Library of Congress' Chronicling America database. My experiments employ a text analysis tool named Voyant, built by Geoffrey Rockwell and Stéfan Sinclair, thereby also offering a basic introduction to the range of visualizations employed in distant reading. My experiments focus on areas in which quantitative methods are particularly well suited to generating new knowledge: corpus-wide visualizations and queries, moving beyond traditional text searching, investigations of music critics' authorial styles and detecting sentiment in reviews, and finally, to geographies of music criticism.